Ki67 proliferative index of the neuroendocrine component drives MANEC prognosis. Issue 5 (May 2018) - Milione, Massimo; Maisonneuve, Patrick; Pellegrinelli, Alessio; Grillo, Federica; Albarello, Luca; Spaggiari, Paola; Vanoli, Alessandro; Tagliabue, Giovanna; Pisa, Eleonora; Messerini, Luca; Centonze, Giovanni; Inzani, Frediano; et al.
Abstract : Mixed adenoneuroendocrine carcinomas (MANECs) are composed of a poorly differentiated neuroendocrine carcinoma (NEC) and a non-neuroendocrine (non-NEC) neoplastic epithelial component, each representing at least 30% of the tumor. At present, prognostic factors for MANECs remain largely unexplored. We investigated the clinical-pathologic features of a large multicenter series of digestive system MANECs. Surgical specimens of 200 MANEC candidates were centrally reviewed; diagnosis was confirmed in 160 cases. While morphology, proliferation (mitotic count (MC), Ki67 index) and immunophenotype (p53, SSTR2a, beta-Catenin, Bcl-2, p16, Rb1, ALDH, mismatch repair proteins and CD117) were investigated separately in both components, genomic ( TP53, KRAS, BRAF ) alterations were searched for on the entire tumor. Data were correlated with overall survival (OS). MANEC sites were: 92 colorectal, 44 gastroesophageal and 24 pancreatobiliary. Median OS was 13.2 months. After adjustment for primary site, Ki67 index of the NEC component (but not of the non-NEC component) was the most powerful prognostic marker. At multivariable analysis, patients with Ki67 ≥ 55% had an 8-fold risk of death (hazard ratio (HR) 7.83; 95% confidence interval (CI) 4.17–14.7; P < 0.0001) and a median OS of 12.2 months compared to those with Ki67 < 55% (median OS 40.5 months). MC (HR 1.51; 95% CI 1.03–2.20, P = 0.04) was a weaker prognostic index. Colorectal primary site (HR 1.60; 95% CI 1.11–2.32; P = 0.01) was significantly associated with poorer survival. No single immunomarker, in either component, was statistically significant. This retrospective analysis of a large series of digestive system MANECs, showed that the NEC component, particularly its Ki67 index, was the main prognostic driver.